Loss of MAPK Pathway Activation in Post-Mitotic Retinal Cells as Mechanism in MEK Inhibition-Related Retinopathy in Cancer Patients. Issue 18 (May 2016) - van Dijk, Elon H. C.; Duits, Danique E. M.; Versluis, Mieke; Luyten, Gregrorius P. M.; Bergen, Arthur A. B.; Kapiteijn, Ellen W.; de Lange, Mark J.; Boon, Camiel J. F.; van der Velden, Pieter A.
Abstract : Abstract: Recently, treatment with MEK inhibitors has been shown to be an effective treatment option for metastatic melanoma. Treatment efficacy is dependent on inhibition of MAPK-related melanoma proliferation. However, targeting of MEK can be accompanied by a time-dependent and reversible serous retinopathy of unknown origin. We analyzed the molecular mechanism by which the MEK inhibitor binimetinib may lead to retinopathy, using neuroretina and cell models of retinal pigment epithelium (RPE). Binimetinib inhibited the MAPK pathway while discontinuation of treatment resulted in reactivation. However, cell proliferation was not inhibited correspondingly during binimetinib treatment of ARPE19 cells. Remarkably, post-mitotic neuroretinal tissue displayed a strong MAPK activation that was lost after binimetinib treatment. We propose that binimetinib-associated retinopathy is correlated with inhibition of the MAPK pathway in multiple retinal components. Retinal cells are able to regain the activation after binimetinib treatment, mimicking the reversibility of the retinopathy. As most retinal cells are nonregenerating, other mechanisms than stimulation of proliferation must be involved.